Proposed framework regarding management of patients with breast cancer and anti-cancer treatment-related elevation in cardiac troponin - Michael Cronin; Dina Neiroukh; Aoife Lowery; William Wijns; Michael Kerin; Maccon Keane; Silvie Blazkova; Osama Soliman (International Journal of Cardiology: Heart & Vasculature)
Cardiac biomarkers are a vital component within the first edition of the European Society of Cardiology guidelines in Cardio-Oncology. Specifically, they are mentioned in the definition of mild asymptomatic cancer therapy-related cardiac dysfunction, where left ventricular systolic function is ≥50 % with two outcomes; either a new decrease in global longitudinal strain >15 % from baseline and/or a new rise in cardiac biomarkers above the defined 99th percentile cut off values. Cardiac troponin is one such biomarker.Many of the treatments for breast cancer have published data on cardiac dysfunction and/or cardiovascular toxicity, and such may lead to an elevation in cardiac troponin. However, there is conflicting and incomplete data regarding how to approach an elevated cardiac troponin during anti-cancer treatment, which has confounded patient care in the clinical trial setting.We propose a novel framework to guide physicians in treatment-related elevation of cardiac troponin in the breast cancer population. Secondly, the additive role which the recommendation that cardiac troponin carries within mild asymptomatic definitions of CTRCD is the subject of great debate. We suggest a reflection on the role of biomarkers, specifically in reference to cardiac troponin.